What happens when students do tasks? A comparative, reflective study of student-centred activities in foreign-language classrooms in higher education - Maijala Minna; Joanne Pagèze; Laura Hoskins (39-52, 2022)
This article reports on a small‐scale action‐research project carried out across two higher
education contexts, in Finland and in France, with learners of German (as L3) and English (as L2) respectively.
The aim of the project was to explore how students get into and stay in student‐centred activities and the
use of target language throughout these. Through this small‐scale action research project we sought to
explore the match or mismatch between expectations of what language learning activity types bring learners
and the various language mediations we observed in our FL/ESP classrooms.
Keywords: German as a foreign language learning; English for Specific Purposes; language learning in higher
education; action research; student‐centred activities.